Hepatitis B virus: predominance of genotype D in primitive tribes of the Andaman and Nicobar islands, India (1989-1999) - Arankalle, V A; Murhekar, K M; Gandhe, S S; Murhekar, M V; Ramdasi, A Y; Padbidri, V S; Sehgal, S C (Journal of general virology, 2003)
To understand the possible origin of hepatitis B virus (HBV), three of the four hyperendemic, primitive accessible tribes of the Andaman and Nicobar islands, India, were investigated. The Nicobarese tribe was investigated in 1989 and 1999. The S gene from 65 HBV isolates was amplified by PCR and sequenced. Genotyping and serotyping were carried out on the basis of phylogenetic and amino acid analyses of S gene. All 20 Nicobarese-89 isolates, nine Onges-99 isolates and the single Andamanese-99 HBV isolate were classified as genotype D. Of the Nicobarese-99 isolates, 32 (91.4 %) and three (8.6 %) were genotypes D and A, respectively. Per cent nucleotide identity between the S sequences representing different tribes varied from 98.06 to 98.59 % and varied from mainland isolates by 1.6-2.0 %. Although southeast Asian origin is postulated for the Nicobarese tribe, the presence of different genotypes suggests introduction of HBV after migration to these islands, probably from mainland India, 200 years back, when these islands became inhabited as a part of penal settlement during the British regimen.